In situ observation of deformation processes in nanocrystalline face-centered cubic metals - Kobler, Aaron; Brandl, Christian; Hahn, Horst; Kübel, Christian (Beilstein Journal of Nanotechnology, 2016)
The atomistic mechanisms active during plastic deformation of nanocrystalline metals are still a subject of controversy. The recently developed approach of combining automated crystal orientation mapping (ACOM) and in situ straining inside a transmission electron microscope was applied to study the deformation of nanocrystalline PdxAu1−x thin films. This combination enables direct imaging of simultaneously occurring plastic deformation processes in one experiment, such as grain boundary motion, twin activity and grain rotation. Large-angle grain rotations with ≈39° and ≈60° occur and can be related to twin formation, twin migration and twin–twin interaction as a result of partial dislocation activity. Furthermore, plastic deformation in nanocrystalline thin films was found to be partially reversible upon rupture of the film. In conclusion, conventional deformation mechanisms are still active in nanocrystalline metals but with different weighting as compared with conventional materials with coarser grains.
Keywords: ACOM-STEM; deformation mechanisms; in situ straining; nanocrystalline metals; orientation mapping; quantitative crystallographic analysis